Implementasi Etika Bisnis Islam Terhadap Pembatalan Sepihak Aplikasi Gojek Menu Go Food - Novia Silviani (Institut Agama Islam Tribakti Kediri, 2020)
The purpose of the researcher is to find out the unilateral cancellation made by consumers when ordering food or drinks on the menu Go Food the application Gojek. Researchers use qualitative research based on empirical field and juridical data, the research method is social legal research. This research concludes that the practice of unilateral cancellation carried out by consumers has various reasons and factors that support the occurrence of unilateral cancellations and cause losses to Gojek drivers, unilateral cancellations are not only carried out by consumers but also by Gojek drivers because the application Gojek is experiencing an error. also inflicts harm on himself. The practice of cancellation by consumers on the menu Go Food is an act of breaking promises because consumers do not keep their promises to pay for their orders so that there is no loss between consumers and Gojek drivers. There is no sense of responsibility given by consumers to Gojek drivers so that one-sided cancellations will repeat itself, consumers should have a good attitude when purchasing so that Gojek drivers get wages from consumers. Islamic business ethics sees the practice of one-sided cancellation from consumers is not justified, because in Islamic business it cannot be mutually beneficial and should be mutually beneficial. The attitude of consumers who make this unilateral cancellation is not encouraged by Islamic business ethics.